Receptive and expressive vocabulary among primary one children: a comparison between Malay and English - Lau, Lee Yin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Vocabulary acquisition is an important process to assist children’s reading skill. This is due to the strong relation between vocabulary knowledge (e.g., receptive and expressive vocabulary) and the Simple View of Reading (SVR) model. This study compared the receptive and expressive vocabulary in Malay and English. The children’s first, second and third languages were also investigated in this study. Data on Primary 1 children (N = 866) were analyzed by using a one sample t-test analysis and descriptive statistics. The results showed that most of the Primary 1 children’s receptive and expressive vocabulary was better in Malay than in English. In addition, most of the children’s first language was Sarawak Malay, their second language was Malay, and their third language was English. This shows that the children’s first and second languages were better than their third language because their Malay was better than English. So, most of the children have poor English because English is not their first language. These results also highlight the importance of the English vocabulary acquisition among the children, which will influence their later performance in English.